2020
DOI: 10.1103/physrevb.101.115404
|View full text |Cite
|
Sign up to set email alerts
|

Quantum control of nonlinear thermoelectricity at the nanoscale

Abstract: We theoretically study how one can control and enhance nonlinear thermoelectricity by regulating quantum coherence in nanostructures such as a quantum dot system or a single-molecule junction. In nanostructures, the typical temperature scale is much smaller than the resonance width, which largely suppresses thermoelectric effects. Yet we demonstrate one can achieve a reasonably good thermoelectric performance by regulating quantum coherence. Engaging a quantum-dot interferometer (a quantum dot embedded in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Kondo effect [22,23,28,50,51], energy spectrum of the QD [40,43,48], electron-phonon interactions [44,54,55], and the Fano effect [56][57][58] on the thermoelectric properties of QD heat engines has also been investigated in the linear and non-linear regime. Krawiec et al [41] studied the influence of asymmetric dot-reservoir coupling (Γ L = Γ R ) on thermoelectric properties and showed that in the linear regime, the thermopower S and figure of merit ZT are unaffected by asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Kondo effect [22,23,28,50,51], energy spectrum of the QD [40,43,48], electron-phonon interactions [44,54,55], and the Fano effect [56][57][58] on the thermoelectric properties of QD heat engines has also been investigated in the linear and non-linear regime. Krawiec et al [41] studied the influence of asymmetric dot-reservoir coupling (Γ L = Γ R ) on thermoelectric properties and showed that in the linear regime, the thermopower S and figure of merit ZT are unaffected by asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the special profile of Fano and hybrid resonances as well as its impact on the transport properties of bilayer graphene barrier structures, we can expect high values for the Seebeck coefficient, power factor and ZT . Actually, there are several reports in the literature in which is well-documented how Fano resonances enhance thermoelectricity 42 47 . The typical systems consist of quantum-dot interferometers, molecular junctions and chain junctions to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…This confirms consistency between all methods at weak enough phonon coupling strength, and highlights the limitations of the WCME as the phonon coupling is increased. For all methods we employ counting statistics techniques [15,24,25,[44][45][46] to calculate the transport cumulants necessary to evaluate the thermoelectric power output, noise, and efficiency.…”
Section: Introductionmentioning
confidence: 99%